1980
DOI: 10.1016/s0022-5347(17)55642-6
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection with Atypical Mycobacteria

Abstract: We present a case of disseminated atypical mycobacterial (Mycobacterium intracellularis) infection of the urinary tract. The patient had anhydrous ectodermal dysplasia and an unrelated defect in cell-mediated immunity. The infection resulted in a lengthy ureteral stricture with resultant hydronephrosis and diminished kidney function. A review of the literature revealed only 13 previous cases of atypical mycobacterial infection of the urinary tract. It is important to distinguish between simple colonization by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Such disseminated disease is a common occurrence in patients with AIDS and is frequently due to M. avium-intracellulare (Smith and Grange, 1989). Similar disseminated disease with mycobacteria in the urine, usually this species or M. kansasii, has been reported in pancytopenic patients (Kilbridge er al., 1967;Listwan et al, 1975;Thomas et al, 1980), in those with congenital defects in cell mediated immunity (Thomas et al, 1980) and also in a patient with no identified underlying cause (Phillips and Larkin, 1964).…”
Section: Discussionmentioning
confidence: 99%
“…Such disseminated disease is a common occurrence in patients with AIDS and is frequently due to M. avium-intracellulare (Smith and Grange, 1989). Similar disseminated disease with mycobacteria in the urine, usually this species or M. kansasii, has been reported in pancytopenic patients (Kilbridge er al., 1967;Listwan et al, 1975;Thomas et al, 1980), in those with congenital defects in cell mediated immunity (Thomas et al, 1980) and also in a patient with no identified underlying cause (Phillips and Larkin, 1964).…”
Section: Discussionmentioning
confidence: 99%
“…Most cases that have been documented of genitourinary NTM showed increased prevalence in women. Infections are more common in the elderly population, although a case of genitourinary MAC associated with disseminated infection has been reported in a child as young as 14 years [19]. Genitourinary infection does not appear to be isolated to the immunocompromised, as only one infection in a transplant recipient has been documented [20].…”
Section: Mycobacterial Genitourinary (Gu) Infections: Clinical Presentationmentioning
confidence: 99%
“…While it is not always clear that the presence of these pathogens in a urine culture is necessarily reflective of true infection, in several cases there has been clinical evidence of true disease, and antimicrobial treatment led to culture sterilization and clinical improvement (Table 3) [20,[28][29][30][31][32]. Urinary involvement with disseminated spread has been associated with underlining cell-mediated immune deficiencies or serum interferon-Y-neutralizing autoantibodies [19,28]. None of the patients appear to have any history of HIV which has been associated with disseminated MAC.…”
Section: Mycobacterial Genitourinary (Gu) Infections: Clinical Presentationmentioning
confidence: 99%